Profil pasien preeklamsia berat dan eklamsia di ICU dan HCU RSUP Prof. Dr. R. D. Kandou Manado - Patty, Vania Nita; Lalenoh, Diana Ch.; Wuisan, Debby D. (Universitas Sam Ratulangi, 2016)
Abstract: Preeclampsia was defined as hypertension in pregnancy that occurs after 20th weeks of pregnancy meanwhile eclampsia is the new onset of a grand mal seizure activity and is one of the complications of preeclampsia. Preeclampsia and eclampsia are still the major causes of high maternal and infant mortality in Indonesia (1.5% -25%). Severe preeclampsia becomes an indication of obstetric patients to be admitted to ICU. This study was aimed to obtain the profile of patients with severe preeclampsia and eclampsia admitted to the ICU and HCU Prof. Dr. R.D. Kandou Hospital. This was a descriptive retrospective study. Data were obtained from the medical records of patients admitted to the ICU and HCU from September 2014 to August 2016. There were 33 patients that met the inclusion criteria consisted of 11 patients (33%) with severe preeclampsia and 22 patients (67%) with eclampsia. Most patients were aged â‰¤ 25 years and the median length of stay in this study was 2 days. HELLP syndrome was found in 9 patients (27.3%) and DIC in 1 (3%) patient. There were five patients with ventilator and three patients died due to eclampsia. Conclusion: Most patients in this study were patients with eclampsia and the mortality rate was 9.1%.Keywords: severe preeclampsia, eclampsia, ICU, HCUÂ Abstrak: Preeklamsia didefinisikan sebagai hipertensi dalam kehamilan yang terjadi setelah minggu ke- 20 kehamilan, sedangkan eklamsia adalah onset baru aktifitas kejang grand mal dan merupakan salah satu komplikasi dari preeklamsia. Preeklamsia dan eklamsia masih menjadi penyebab utama tingginya angka kematian ibu dan bayi di Indonesia (1,5%-25%). Preeklamsia berat menjadi indikasi pasien obstetri masuk ke ICU. Penelitian ini bertujuan untuk mengetahui gambaran pasien preeklamsia berat dan eklamsia yang dirawat di ICU dan HCU RSUP Prof. Dr. R.D. Kandou. Jenis penelitian ialah deskriptif retrospektif. Data diperoleh melalui data rekam medik pasien yang dirawat di ICU dan HCU periode September 2014 - Agustus 2016 dan didapatkan sebanyak 33 pasien yang memenuhi kriteria inklusi. Total pasien preeklamsia berat ialah 11 orang (33%) dan eklamsia sebanyak 22 orang (67%). Usia â‰¤25 tahun ialah usia terbanyak dan median lama rawat dalam penelitian ini ialah 2 hari. Kejadian HELLP syndrome pada kasus ini sebanyak 9 orang (27,3%) dan DIC sebanyak 1 orang (3%). Pasien dengan ventilator sebanyak 5 orang dan pasien yang meninggal akibat eklamsia sebanyak 3 orang. Simpulan: Dalam penelitian ini pasien terbanyak ialah pasien eklamsia dengan angka kematian 9,1%. Kata kunci: preeklamsia berat, eklamsia, ICU, HCU